(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
A new species of Italian tortricid moth, Pelochrista cannatana sp.n. from Sicilia, is described. Externally the new species resembles Pelochrista huebneriana (Zeller, 1846) and P. infidana (Hiibner, 1824). In male genitalia it is similar to P. caecimaculana (Hiibner, 1796-99), the differences are small, seen in the size of socius longer in P. cannatana, in neck of valvae more distinct in P. caecimaculana, in apex of sacculus less pronounced than in P. caecimaculana. The female genitalia of P. cannatana and P. caecimaculana are very similar to one another, the main differences are in ostium bursae, sterigma and corpus bursae more developed in P. cannatana. Notes on 16 species of Pelochrista Lederer, 1859, of the Italian fauna are also reported.